The Effectiveness of Scaffolding Method in Improving Students' Arabic Essay Writing Competence - Renti Yasmar; Rahadian Kurniawan (Universitas Negeri Semarang, 2025)
This study explores the effect of the Scaffolding Method to improve students' Arabic Essay Writing Competence. This study used an experimental strategy with a one-group pretest–posttest design in order to measure changes in performance within the same cohort. The results show that the students' writing skills have significantly improved from their initial assessment scores (68.50) to their final evaluation scores (85.75), with the latter showing a lower standard deviation, indicating greater consistency in performance. The paired samples test findings show a t-value of -8.358 with p < 0.001, which supports the difference's statistical significance. These discoveries affirm that scaffolding represents a beneficial pedagogical approach for enhancing students' essay writing skills, presenting a tangible resolution for the instruction of Arabic essay composition. Beyond statistical gains, the findings also highlight that the method helps students engage more actively in the learning process, fosters confidence in structuring ideas, and gradually reduces reliance on teacher guidance. Nevertheless, this study is limited by the small number of participants and its focus on a single program of study. Future research is recommended to involve larger and more diverse samples and to explore the effectiveness of scaffolding in various other educational contexts and text genres.